Formation of healthy psychological structures: affections as a source of stimulation - Leiva Meza, Martha Inés (2008)
This project begins with prenatal sensory stimulation in order to improve the baby´s quality of life, finding ways to manage the pregnant´s tranquility, returning better levels of emotional stability and controlling high levels of hormones related to stress which alter the organization of the baby´s neurological maturing, as well as contributing to produce well-being hormones which strengthen cerebral maturity. This also contributes to child formation at early ages developing his/her psychological maturing, taking into account the configuration of affections in the mother, the child, the couple as well as search of the family unity. The main objective is prenatal and postnatal development of the child and it  involves the pilars related to his/her development, which are the mother, the father, the couple and the family